2010
DOI: 10.1159/000320784
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Integrin α<sub><i>v</i></sub> Signaling Pathway in Uterine Leiomyomas

Abstract: Objective: To investigate alterations of integrin αv, survival and apoptosis signaling pathways in uterine leiomyomas. Materials and Methods: In a prospective study of 50 women with uterine leiomyomas that had been pathologically confirmed, specimens were obtained laparoscopically from 2007 to 2009. The expressions of integrin αv signaling pathways (Ras/Raf/ERK1/2, Akt and cleaved caspase-3), surface microstructures by surface electron microscopy and immunohistochemical findings were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…This enzyme catalyzes the posttranslational formation of 4‐hydroxyproline in ‐Xaa‐Pro‐Gly‐ sequences in collagens and excessive collagen production is a hallmark of fibrotic conditions including uterine fibroids. Three integrins (ITGA3, ITGA7, and ITGB1) are downregulated in myoma that is consistent with independent earlier findings on integrin alpha signaling in this disease . Similarly, as noted before , we observe a clear reduction in the levels of Retinal dehydrogenase 1, (ALDH1A1) the enzyme producing the low molecular weight molecule retinoic acid that regulates the transcription of a number of developmental genes, possibly also in leiomyoma.…”
Section: Resultssupporting
confidence: 92%
“…This enzyme catalyzes the posttranslational formation of 4‐hydroxyproline in ‐Xaa‐Pro‐Gly‐ sequences in collagens and excessive collagen production is a hallmark of fibrotic conditions including uterine fibroids. Three integrins (ITGA3, ITGA7, and ITGB1) are downregulated in myoma that is consistent with independent earlier findings on integrin alpha signaling in this disease . Similarly, as noted before , we observe a clear reduction in the levels of Retinal dehydrogenase 1, (ALDH1A1) the enzyme producing the low molecular weight molecule retinoic acid that regulates the transcription of a number of developmental genes, possibly also in leiomyoma.…”
Section: Resultssupporting
confidence: 92%
“…No significant difference was observed in the expression of these pro-survival factors between UL and MM. Similar pAkt expression in UL and normal myometrial tissue has been reported by other researchers222324. Further, pAkt expression was low or absent in a large number of leiomyoma samples (73%) in our study, a finding supported by another study25.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence for the interaction between serotonin (5-hydroxytryptamine, 5-HT) and thyroid hormones originates mostly from the experimentally induced hypothyroid state in animals [3]. Decreased 5-HT [7, 8] and increased 5-hydroxyinoleacetic acid [9] concentrations were observed in neonatal and adult hypothyroid rats, suggesting an increased 5-HT turnover [7, 10], while T 3 administration to hypothyroid animals normalized 5-HT turnover to normal values [10]. …”
Section: Introductionmentioning
confidence: 99%